2010
DOI: 10.1007/s12310-010-9042-5
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Prevalence of Anxiety in Children and Adolescents: An Evaluation of the Evidence Base for the FRIENDS for Life Program

Abstract: Current estimates suggest that between 8 and 22% of children and adolescents may suffer from an anxiety disorder. Effective intervention efforts are therefore clearly needed to reduce the likelihood of anxious symptoms and promote healthy functioning. One intervention that appears feasible for use in schools and was designed to target anxiety symptoms is the FRIENDS for Life program. Evaluation of FRIENDS has been limited in the United States; however, criteria for evaluation of such programs are available. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 45 publications
(62 reference statements)
1
31
0
3
Order By: Relevance
“…Delivering programs in school settings within regular school hours increases the accessibility and integration of mental health services within the existing school ecology . Not only does the school setting represent a powerful venue to deliver mental health services, but, consistent with the results of this study, students are likely to find the supports to be acceptable and the skills as useful in their lives.…”
Section: Discussionsupporting
confidence: 69%
“…Delivering programs in school settings within regular school hours increases the accessibility and integration of mental health services within the existing school ecology . Not only does the school setting represent a powerful venue to deliver mental health services, but, consistent with the results of this study, students are likely to find the supports to be acceptable and the skills as useful in their lives.…”
Section: Discussionsupporting
confidence: 69%
“…We consulted repositories of EBPs (e.g., http://nrepp.samhsa.gov/landing.aspx, http://www.ebbp.org) and meta‐analyses of group treatments (e.g., Briesch, Sanetti, & Briesch, ) to identify group‐based interventions that could be used at Tier 2. We examined the literature on mental health promotion in children (e.g., Durlak, Domitrovich, Weissberg, & Gullotta, ; Weisz, Sandler, Durlak, & Anton, ) and identified programs that emphasize the teaching of anger management, problem‐solving, social awareness and relationship building.…”
Section: Methodsmentioning
confidence: 99%
“…FRIENDS (Barrett, 2008) has been shown to be effective for the prevention and treatment of anxiety disorders (Briesch, Sanetti, & Briesch, 2010). For example, in a randomized trial with children diagnosed with an anxiety disorder, 69% of children assigned to FRIENDS were diagnosis free at the end of the 10-week trial compared with 6% of children assigned to a wait-list condition (Shortt, Barrett, & Fox, 2001).…”
Section: Effective Interventions In the School Settingmentioning
confidence: 99%
“…For example, in a randomized trial with children diagnosed with an anxiety disorder, 69% of children assigned to FRIENDS were diagnosis free at the end of the 10-week trial compared with 6% of children assigned to a wait-list condition (Shortt, Barrett, & Fox, 2001). It has been shown that FRIENDS is an effective school-based intervention for at-risk children as well as for children who meet diagnostic criteria for an anxiety disorder (Briesch et al, 2010). …”
Section: Effective Interventions In the School Settingmentioning
confidence: 99%